Citra Merek dan Kualitas Produk terhadap Minat Beli Ulang pada Teh Pucuk Harum di Kota Bandung - Nursaidah, Nazalina Fitri; Nurtjahjadi, Edi (Journal of Management and Bussines (JOMB), 2024)
The purpose of this study is to examine the effect of brand image and product quality on repurchase intention of Pucuk Harum tea in the city of Bandung. This research instrument has gone through the stages of validity and reliability testing, classical assumption testing, and multiple regression testing. This study will involve samples and consumer populations with an age range of 17 to 56 years. The focus of the research area is the city of Bandung, where Pucuk Harum tea products are products that are already well-known in the city of Bandung and are the objects of this study. The number of samples in this study was set at a minimum of 120 people. This type of research uses a quantitative approach. The analysis tool used to test the data instrument uses SPSS software version 25. The results of the study indicate that brand image and product quality have a positive and significant effect on repurchase intention simultaneously, this study is expected to be useful for managers of objects that are assessed regarding the design of relevant strategies or programs. Keywords: Brand Image, Product Quality, Repurchase Intention